Methodological Bases with Professional Terms in Non-Philological Directions of Universities (On the Example of Russian Language) (Global Scientific Review, 2023)
This article examines the study of architectural and construction terms and terminology in the classroom of the Russian language in non-philological areas of universities. With the help of interactive methods, we work with professional terms (terminology).